GROUPS AND THEIR EFFECTS IN ORGANIZATIONS - AscÄ±, Mehmet Saim; Cemberci, Murat; Civelek, Mustafa Emre; Gunel, Deniz (European Scientific Journal, ESJ, 2015)
The human is a social being and survives as the part of a group in every field of life from the birth. Group is a community consisting of one or more individuals who interact with each other in order to accomplish a certain goal. The groups are created formally and informally within the organization at different times and for different goals. Those groups have the negative and positive influences on the organization structure and function. In this work, the group concept in the organizations is studied and the influence of group behaviors within the organizations is discussed conceptually.